2015
DOI: 10.1002/lary.25421
|View full text |Cite
|
Sign up to set email alerts
|

Allergic reaction to ortho‐phthalaldehyde following flexible laryngoscopy

Abstract: Flexible laryngoscopes are common outpatient surveillance tools. Cleansing of these scopes between patients must be quick, effective, and safe. One sterilant that largely meets these criteria is ortho-phthalaldehyde (OPA); however, infrequently, patients may develop allergic reactions to it. We present three cases of patients who developed significant allergic reactions following repeated laryngoscopic examinations. Subsequent intradermal allergy testing confirmed sensitivity to OPA. In addition, we reviewed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…25 However, recent research has raised new toxicity concerns for ortho-phthalaldehyde as a substitute, 26 because its adhesive nature has led to reports of anaphylactic shock from residual on endoscopes. 27 The micellized nature of Microbide's products eliminates adhesion, and thus, demonstrates clear advantages for infection control. Microbide-O outperformed Cidex ® OPA at both temperatures by successfully disinfecting more carriers overall and failing just one test compared to Cidex ® OPA, which failed three tests ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…25 However, recent research has raised new toxicity concerns for ortho-phthalaldehyde as a substitute, 26 because its adhesive nature has led to reports of anaphylactic shock from residual on endoscopes. 27 The micellized nature of Microbide's products eliminates adhesion, and thus, demonstrates clear advantages for infection control. Microbide-O outperformed Cidex ® OPA at both temperatures by successfully disinfecting more carriers overall and failing just one test compared to Cidex ® OPA, which failed three tests ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Specific to otolaryngology, three cases of OPA‐induced anaphylaxis have been reported in the literature from patients undergoing serial laryngoscopy for head and neck cancer surveillance . Three additional cases recently were reported, and a literature review identified 17 reactions in nine patients across surgical specialties . Although quite rare, an allergic reaction to the sterilant likely is underrecognized and may well increase with growing awareness of this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…11 Three additional cases recently were reported, and a literature review identified 17 reactions in nine patients across surgical specialties. 12 Although quite rare, an allergic reaction to the sterilant likely is underrecognized and may well increase with growing awareness of this possibility. The Medicine and Healthcare products Regulatory Agency in the United Kingdom has gone so far as to recommend the use of a validated alternative to OPA due to the difficulty in rinsing and the risk of anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate-type hypersensitivity reactions during cystoscopy and laryngoscopy with orthophthaldehyde have been reported. 82 , 83 , 84…”
Section: Antiseptics Disinfectants and Sterilizing Agentsmentioning
confidence: 99%